Behavioral and neurobiological changes in C57BL/6 mouse exposed to cuprizone: effects of antipsychotics - Xu, Haiyun; Yang, Hong; McConomy, Bryan; Browning, Ronald A.; Li, Xin-Min (Frontiers in Behavioral Neuroscience, 2010)
Recent human studies suggest a role for altered oligodendrocytes in the pathophysiology of schizophrenia. Our recent animal study has reported some schizophrenia-like behaviors in mice exposed to cuprizone (Xu et al., 2009), a copper chelator that has been shown to selectively damage the white matter. This study was to explore mechanisms underlying the behavioral changes in cuprizone-exposed mice and to examine effects of the antipsychotics haloperidol, clozapine and quetiapine on the changes in the mice. Mice given cuprizone for 14 days showed a deficit in the prepulse inhibition of acoustic startle response and higher dopamine in the prefrontal cortex (PFC), which changes were not seen in mice given cuprizone plus antipsychotics. Mice given cuprizone for 21 days showed lower spontaneous alternations in Y-maze, which was not seen in mice treated with the antipsychotics. Mice given cuprizone for 28 days displayed less social interactions, which was not seen in mice given cuprizone plus clozapine/quetiapine, but was seen in mice given cuprizone plus haloperidol. Mice given cuprizone for 42 days showed myelin sheath loss and lower myelin basic protein in PFC, caudate putamen, and hippocampus. The white matter damage in PFC was attenuated in mice given cuprizone plus clozapine/haloperidol. But the white matter damage in caudate putamen and hippocampus was only attenuated by clozapine and quetiapine, not by haloperidol. These results help us to understand the behavioral changes and provide experimental evidence for the protective effects of antipsychotics on white matter damage in cuprizone-exposed mice.